Complex Odontoma: An Overview - Somalee Mahapatra1 , Priyanka Debta2 , Saswati Siddhartha3 , Anurag Dani4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The dental tissues comprising of dentin, enamel,sometimes pulp, and cementum are the hamartomas whichare known as odontoma. These have behavior not so aggressive. The common type of tumor of odontogenicorigin about (35-76)% is the odontoma. It is a tumor of benign type arising from epithelial and mesenchymaldifferentiated alteration, odontogenic cells. These odontomas are of two types–complex and compound,the both are differentiated from each other by the organization of the tissue of dental origin in a ratio of1:2. Although the etiology is not known till now but may be related to anomalies of hereditary origin,infection,also by trauma and by hyperactivity of odontoblast process. By the means of radiological viewthese odontomas can be recognized and these in very few case causes expansion of the cortical bone. Theseodontomas occur in the second decade in number and usually takes place in the mandibular second or thirdmolar tooth. This particular article summarizes the complex composite odontoma.